Diffuse fraction estimation using the BRL model and relationship of predictors under Chilean, Costa Rican and Australian climatic conditions. (June 2019) - Rojas, Redlich García; Alvarado, Natalia; Boland, John; Escobar, Rodrigo; Castillejo-Cuberos, Armando
Abstract: In this paper a model is used to estimate the diffuse radiation using the Boland-Ridley-Lauret (BRL) model, which is developed for Chile, Costa Rica, and Australia. Additionally, artificial Direct Normal Irradiance time series are determined from the diffuse fraction results estimated by the model. Both estimates achieve excellent agreement based on the bias and normalized scatter. The relationship between the predictors of the model and the climatic conditions of each case of study, according to the Köppen-Geiger climatic classification was analyzed, which to the best of the authors' knowledge, it's the first study of this kind. An analysis on correlation and statistical significance was carried out between the model predictors and four determining geographic and climatic variables: altitude, latitude, precipitation and temperature. The statistical analysis shows that two of the six predictors correlate with temperature and precipitation and one predictor is correlated with latitude. Therefore, it can be suggested that the BRL model seems largely insensitive to the different regional climatic conditions, nevertheless, evaluation of the effect of the apparent correlation of the respective predictors and microclimatic and geographical variables points to further research in this area considering a wider selection of locations. Highlights: The BRL model predictors were calculated for Chile, Australia and Costa Rica. Diffuse irradiance and DNI estimations were performed from GHI measurements. The observed bias, as well as normalized scatter, were fairly low for hourly data. BRL model predictors were correlated against the Köppen – Geiger climatic classification. A non-negligible correlation was found between predictors and precipitation, temperature and latitude.